2002
DOI: 10.1002/dev.10069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neonatal handling and maternal separation on rough‐and‐tumble play in the rat

Abstract: The extent to which brief daily handling and longer periods of separation from the mother during the first 2 weeks of life can affect play behavior in juvenile rats was assessed. Rat pups were separated from the mother for either 15 min daily (handling) or for 3 hr daily (maternal separation), and play was observed as juveniles. Overall levels of playfulness were not affected by either manipulation, although certain aspects of playful responsiveness were affected in males, but not females. In particular, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
1
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 58 publications
3
32
1
4
Order By: Relevance
“…Food and water continued to be freely available and the 12-hour light/dark cycle was maintained. A recent paper from our laboratory reported that this separation protocol of 6 hours per day for 10 days during Postnatal Days 2-13 resulted in behavioral hyperactivity/impulsivity in adolescent male SpragueDawley rats [6], a phenotype which is consistent with other similar studies [2,5,16,35]. We used the same separation procedures in this study to verify that maternal separation increases ambulatory behavior in the novel open field test [6].…”
supporting
confidence: 69%
“…Food and water continued to be freely available and the 12-hour light/dark cycle was maintained. A recent paper from our laboratory reported that this separation protocol of 6 hours per day for 10 days during Postnatal Days 2-13 resulted in behavioral hyperactivity/impulsivity in adolescent male SpragueDawley rats [6], a phenotype which is consistent with other similar studies [2,5,16,35]. We used the same separation procedures in this study to verify that maternal separation increases ambulatory behavior in the novel open field test [6].…”
supporting
confidence: 69%
“…In a similar way, rat pups, weaned earlier by mothers that were food restricted or pregnant during lactation, showed play-fighting behaviors more frequently than those reared and normally weaned by mothers that were given food ad libitum (Smith, 1991). On the other hand, another study showed that brief daily handling or longer periods of separation from mother during the first 2 weeks of life did not affect levels of playfulness in juvenile rats (Arnold & Siviy, 2002). These conflicting results indicate that the effects of early environmental manipulations on play behavior vary depending on differences of experimental designs and species.…”
Section: Discussionmentioning
confidence: 82%
“…Prenatal stress of the dams through restraint stress leads to a feminization of social play patterns in males with no effect on females (Ward & Stehm, 1991). Male rats exposed to either handling or maternal separation showed a more feminized pattern of play behavior (Arnold & Siviy, 2002). An acute impoverishment of the environment through food restriction increases play when the restriction is imposed acutely before play fighting is observed (Siviy & Panksepp, 1985).…”
Section: Introductionmentioning
confidence: 95%